Pluronic lecithin organogel of 5-aminosalicylic acid for wound healing. (3rd October 2018) - Sanapalli, Bharat Kumar Reddy; Kannan, Elango; Balasubramanian, Shivaramakrishnan; Natarajan, Jawahar; Baruah, Uday Krishna; Karri, Veera Venkata Satyanarayana Reddy
Abstract: 5-Aminosalicylic acid (5-ASA) is an aminosalicylate anti-inflammatory drug, which is also known as mesalazine or mesalamine. Currently employed in treating inflammatory bowel disease, ulcerative colitis, inflamed anus or rectum, and maintain remission in Crohn's disease. Evidence from the researchers highlighted its significant re-epithelization in allergic asthma, aphthous, and gastric ulcerative conditions. The objective of the study was to formulate the pluronic lecithin organogel (PLO) containing 5-ASA and evaluate its wound-healing ability in a full thickness excision wound rat model. The data obtained from in silico docking studies revealed 5-ASA is having an affinity towards the transforming growth factor-beta (TGF-β) specifically towards beta1. Among various formulations prepared (F1 to F8), F1, and F6 have shown a maximum in vitro drug release with optimum pH and viscosity. From MTT assay it was found that selected PLO formulations showed no toxicity and enhanced cell proliferation in HaCaT cell lines. In vivo wound-healing studies in albino Wistar rats has revealed that PLO accelerates wound closure and reepithelization to the statistically significant level on day 3 ( p < .05) in comparison with untreated wounds. In conclusion, the overall results suggest that 5-ASA PLO gel is a potential therapeutic option for the treatments of wounds, however, further studies are highly warrened to determine the various mechanisms of 5-ASA in regulating the cell migration and reepithelization in wound healing to outspread its use in clinics.